MORPHOMETRIC FEATURES OF THE RESTRUCTURING OF RAT SUBMANDIBULAR ACINI UNDER THE INFLUENCE OF A COMPLEX OF FOOD ADDITIVES - Yeroshenko, G.A.; Bieliaiev, I.S.; Shevchenko, K.V.; Klepets, O.V.; Vatsenko, A.V.; Sharlay, N.M.; Pavlyuk, M.M. (World of Medicine and Biology, 2024)
The use of a complex of food additives leads to a change in the structural and functional state of the acini of the submandibular salivary glands of rats, which was expressed by a significant decrease in the morphometric parameters of the outer diameter, inner diameter and height of epithelial cells due to the primary endogenous action of the components of the complex of food additives with an increase in the volume of the interstitium in the early stages of the experiment, but later, the action of compensatory and restorative reactions of the body did not lead to complete recovery, as there was a constant restructuring of the secretory apparatus of seromucous cells, which was confirmed by a significant wave-like increase in the diameter of the outer and height of epithelial cells, against the background of a decrease in the diameter of the lumen. The activation of secretion is associated with the reaction of the submandibular salivary glands to a change in the nature of nutrition associated with the presence of food additives and the restructuring of the base of the serotonergic apparatus in favor of proteins, with the appearance of some areas of complete sloughing, and is a morphological confirmation of the predominance of the carbohydrate component, and is protective in relation to the effect of the components of the food additives complex on the mucous membrane of both the oral cavity, and the initial parts of the gastrointestinal tract.